2023
DOI: 10.1111/os.13780
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Adding Acetaminophen to Preemptive Multimodal Analgesia in Total Knee Arthroplasty: A Double‐blinded Randomized Study

Abstract: ObjectivePreemptive multimodal analgesia is a frequently utilized method for controlling pain after total knee arthroplasty (TKA). So far, no studies have specifically examined the efficacy of adding acetaminophen to preemptive multimodal analgesia in TKA. The current work aimed to assess the efficacy of adding acetaminophen to preemptive multimodal analgesia for clinical pain management after TKA.MethodsThis was a double‐blinded randomized study including 80 cases randomized to the acetaminophen and control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In our study, the patients received a recommended dosage of 500 mg of paracetamol and mannitol injection before one-lung ventilation, with two additional dosage administered 24 h after surgery. In a previous study of total knee arthroplasty, there was no clinical improvements or benefits in patients administered preemptive acetaminophen [ 14 ]. However, a retrospective study including 1416 patients revealed that the pretreatment of acetaminophen and gabapentin 30–60 min prior to operation reduced postoperative opioid requirements and pain [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the patients received a recommended dosage of 500 mg of paracetamol and mannitol injection before one-lung ventilation, with two additional dosage administered 24 h after surgery. In a previous study of total knee arthroplasty, there was no clinical improvements or benefits in patients administered preemptive acetaminophen [ 14 ]. However, a retrospective study including 1416 patients revealed that the pretreatment of acetaminophen and gabapentin 30–60 min prior to operation reduced postoperative opioid requirements and pain [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paracetamol exerts its analgesic effects via different pathways, including the inhibition of COX-2-dependent prostaglandin E2 synthesis, indirectly activating CB1 and TRPV1 receptors in the brain through its metabolites AM404 [ 11 , 12 ]. Multiple studies have shown the positive effect of paracetamol on postoperative pain management in various procedures, including orthopedic surgery, radical mastectomy, cholecystectomy, cesarean section and abdominal hysterectomy [ 13 , 14 ]. However, a previous study involving women receiving hysterectomy revealed that intravenous acetaminophen did not decrease narcotic use or postoperative pain compared with the group that received the placebo [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We obtained this information prior to patient enrollment from patients who were not included in the trial. The materials and methods are partially based on previous studies 22-24 .…”
Section: Methodsmentioning
confidence: 99%